A inovação pedagógica: elo entre a sequência Fedathi, a teoria da objetivação e a insubordinação criativa para uma mudança da prática docente - Scipião, Lara Ronise de Negreiros Pinto (2024)
Pedagogical innovation requires differentiated teaching practices that enable autonomy, engagement, and protagonism of teachers and students during the teaching-learning process. These practices were analyzed based on the experience as a teacher and trainer, through discussions about teaching action and in the extension course <Teacher training according to learning profiles: an experience with the Fedathi Sequence and the Theory of Objectification=. The Fedathi Sequence (FS), as a teaching and data analysis methodology, guides, respectively, pedagogical decisions influenced by the didactic sessions developed and experienced in the teachers' classrooms, and analyzes the research data. The Theory of Objectification (TO) underpins the theoretical framework, enabling reflections on community ethics and joint work, while Creative Insubordination (CI) contributes to the identification of innovativecollaborative practices. In view of this, the proposed research question is: How has the SF/TO/IC triad contributed to the awareness of teachers who teach mathematics in the early years of elementary school in the constitution of innovative-collaborative practices, in the context of the emancipatory teachinglearning process? We aim to analyze the contributions of the SF/TO/IC triad to the awareness of teachers who teach mathematics in the early years of elementary school, favoring innovative-collaborative practices in the emancipatory teaching-learning process. To this end, we defined three specific objectives, organized based on the hypothesis presented, outlining the methodological steps in the investigation. Methodologically, we chose a qualitative, exploratory approach, of the case study type. In procedural terms, the research had four stages: (I) bibliographic study; (II) collaborative study; (III) case study and (IV) the production of the thesis report. We conducted questionnaires and discussions in the forums of the Virtual Learning Environment developed by the Study and Research Group Weaving Cognitive Learning Networks. The course, held in a hybrid format between April and June 2024, had synchronous and asynchronous meetings, totaling a workload of 100 hours, taught by group members. Of the twelve teachers who completed the course, five were selected based on criteria such as: being a teacher with experience in teaching mathematics in the early years, being a teacher in full exercise of activities and assigned to public schools; having a minimum attendance of 75% in participation in the meetings, having carried out the forum activities; as well as having planned and experienced the teaching session in the classroom and; subsequently presented in the course. The results reveal that pedagogical practices based on the triad, combined with interdisciplinary, creative and dynamic actions, helped teachers reflect on the emancipatory teaching-learning process. Furthermore, we found that the development of these actions, through collective planning of the teaching sessions, demonstrated that interactions and discussions among peers enhanced innovative-collaborative practices. We concluded that the research emphasized the originality of the pedagogical approach adopted, promoting reflections based on the activities, discussions, planning and experience of the teaching sessions, based on the triad.